Enhancing Students' Critical Thinking Skills in the Implementation of the Merdeka Curriculum in Madrasah - Abidin, Zaenal; Wiarsih, Nur; Faishol, Riza; Baharun, Hasan (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2024)
This research aims to examine how the Merdeka Curriculum can be implemented at Madrasah to improve student's critical thinking skills without sacrificing Islamic religious education, where this research can make a significant contribution to curriculum development at Madrasah and enrich academic literature on education religion and 21st-century skills. This research uses qualitative with case study. Data collection techniques are through interviews, observation, and documentation. Data analysis includes identifying patterns, themes, and nuances from interviews and observations. The research results show that several things can be implemented several things can be implemented in developing an independent curriculum for madrasas. First, develop material that stimulates critical thinking by connecting theory with everyday situations relevant to students. Second, project-based activities involve students actively in the learning process, where they receive information passively and participate actively in knowledge creation. Third, critical thinking in a spiritual context encourages students to accept religious teachings passively and question and understand more profound meanings. Fourth, Self-Reflection and Metacognition can strengthen students' understanding of the material studied.